Keputusan Berkunjung Ke Taman Nasional Gunung Gede Pangrango Jawa Barat: Pendekatan Analisis Atribut - Malini, Lamtiar Hema; Eddyono, Fauziah; Sulistyadi, Yohanes; Sukwika, Tatan (Jurnal Manajemen, 2023)
National parks have great potential for nature tourism enthusiasts worldwide, including Indonesia. There are 54 national parks spread across Indonesia, and one of them is Mount Gede Pangrango National Park (TNGGP), West Java. TNGGP is one of the many visited by domestic tourists, especially tourists from millennials. This research aims to analyze the behaviour of millennial tourists through the approach of digital promotion attributes, ecotourism attractions and their motivation for visiting decisions. The study used quantitative analysis and randomly selected respondents from as many as 100 tourists. It ended by processing data from the results of distributing questionnaires with the help of Structural Equation Modeling software. The results of the data analysis show that there is an influence of tourist perceptions on ecotourism attractions and tourist motivation on the decision to visit and has an impact on repeat visits to GPNP. However, digital promotion attributes do not influence millennial tourists' decisions to visit TNGGP, let alone to visit repeatedly. This study recommends that managers re-evaluate digital promotion programs to increase visits to TNGGP.